2016
DOI: 10.1074/jbc.m114.624619
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Cooperation of Glucose and Glutamine Is Essential for the Lytic Cycle of Obligate Intracellular Parasite Toxoplasma gondii

Abstract: Toxoplasma gondii is a widespread protozoan parasite infecting nearly all warm-blooded organisms. Asexual reproduction of the parasite within its host cells is achieved by consecutive lytic cycles, which necessitates biogenesis of significant energy and biomass. Here we show that glucose and glutamine are the two major physiologically important nutrients used for the synthesis of macromolecules (ATP, nucleic acid, proteins, and lipids) in T. gondii, and either of them is sufficient to ensure the parasite survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 47 publications
10
68
0
Order By: Relevance
“…S4). An apparent redundancy in L-lactate transport is also in accordance with the exceptional metabolic plasticity observed in the central carbon metabolism of tachyzoites (16,18,19). FNTs discriminate between different monocarboxylate substrates by size selection in the ⌽/K filter region (7).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…S4). An apparent redundancy in L-lactate transport is also in accordance with the exceptional metabolic plasticity observed in the central carbon metabolism of tachyzoites (16,18,19). FNTs discriminate between different monocarboxylate substrates by size selection in the ⌽/K filter region (7).…”
Section: Discussionsupporting
confidence: 67%
“…Besides mere redundancy, it is plausible that they serve different parasite stages during the natural life cycle. Glucose import is critical for Plasmodium species (17,18), whereas T. gondii tachyzoites can survive without it, albeit with a modest growth defect (13,16). In accord with PfFNT, inhibition of the singular hexose transporter in Plasmodium (PfHT) kills the parasite (17,29), validating both PfHT and PfFNT as antimalarial targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While initially thought to have a streamlined metabolism and to be primarily dependent on glycolysis for ATP synthesis [28,29], recent metabolomic profiling and 13 Cglucose/glutamine labeling studies on T. gondii infected human foreskin fibroblasts have shown that intracellular tachyzoites co-utilize host glucose and glutamine and have an active mitochondrial metabolism in which pyruvate/oxaloacetate (derived from glucose) or a-ketoglutarate/g-aminobutyric acid (derived from glutamine) are catabolized in a canonical tricarboxylic acid (TCA) cycle ( Figure 1a). Remarkably, disruption of glucose uptake [30 ] or glutamine deprivation [31] has little effect on tachyzoite proliferation in host cells, suggesting that they are able to readily switch between glycolytic and gluconeogenic metabolic states. Even under conditions where both glucose and glutamine uptake/availability is limited, tachyzoites continue to grow slowly, suggesting that they can use other amino acids or alternative carbon sources, such as acetate/fatty acids [31,32].…”
Section: Link Between Host Cell Range and Parasite Metabolic Plasticitymentioning
confidence: 99%
“…Remarkably, disruption of glucose uptake [30 ] or glutamine deprivation [31] has little effect on tachyzoite proliferation in host cells, suggesting that they are able to readily switch between glycolytic and gluconeogenic metabolic states. Even under conditions where both glucose and glutamine uptake/availability is limited, tachyzoites continue to grow slowly, suggesting that they can use other amino acids or alternative carbon sources, such as acetate/fatty acids [31,32]. The metabolic flexibility of these stages is likely to be an important factor underlying the capacity of tachyzoites to proliferate in many different cell types.…”
Section: Link Between Host Cell Range and Parasite Metabolic Plasticitymentioning
confidence: 99%